Research Progress of Wound Dressing Based on Sodium Alginate Composite Hydrogel - Zhou, Fengchao; Deng, Shibin; Lin, Guorong; Shen, Jiandong; Tang, Dianping (Current Medicinal Chemistry, 2026)
Hydrogel wound dressing has significant advantages in wound treatment. It can shorten the time of wound healing, control the process of wound healing, and effectively promote the healing of damaged tissues in a hydrated environment. Sodium alginate (SA) is a commonly used hydrogel wound dressing material, which can quickly form a three-dimensional network structure hydrogel in a relatively mild environment, but the mechanical properties and stability of a single SA hydrogel are poor. The composite hydrogel prepared by mixing SA with other substances can not only exert the performance of a single substance but also improve the mechanical properties, stability and adsorption of the hydrogel and has a wider application prospect in the field of sustained release control of bioactive substances. Natural polymers have been widely used in the preparation of hemostatic and wound healing materials due to their excellent biocompatibility, degradability, viscoelasticity and easy processing. This paper introduces the research progress of composite hydrogels prepared by SA and natural polymers in mechanical properties, antibacterial, anti-inflammatory, tissue repair and sustained release control of bioactive substances, and provides a theoretical basis for the application of SA-based composite hydrogels in wound dressings.
Keywords: wound dressing; gelatin